PENGARUH KARTU BERGAMBAR TERHADAP KEMAMPUAN MEMBACA SISWA KELAS 1 SEKOLAH DASAR RAHVA MARENDAL 1 TAHUN PELAJARAN 2024-2025 - Priska Yolanda; Zaini Dahlan; Zunidar (Jurnal Riset Multidisiplin Edukasi, 2025)
The number of students who are not yet fluent readers is the focus of this research. First-grade students at Rahva Marindal 1 Elementary School are the subjects of this study, which aims to document their reading comprehension during the 2024–2025 academic year. All twenty-eight first-grade students at Rahva Marindal 1 Elementary School during the 2024–2025 academic year constitute the population of this research. A software package called IBM SPSS Statistics 27 was used to assist with the data analysis process. The first-grade students at SD Marindal 1 showed improvement in their reading comprehension after using picture cards as a teaching aid. The asymp.sig (2-tailed) value was 0.000, as indicated by the "test statistics" output. The decision to reject the null hypothesis (HO) was made because the significance value (0.002) was less than 0.05. This indicates that the post-test results of the observation sample differed significantly from their pre-test scores. In other words, the test scores of first-grade students at Rahva Elementary School were significantly influenced by the use of picture card media.